Molecular Epidemiology of Antibiotic-Resistant Escherichia coli from Farm-to-Fork in Intensive Poultry Production in KwaZulu-Natal, South Africa - Katherine S. McIver; Daniel Gyamfi Amoako; Akebe Luther King Abia; Linda A. Bester; Hafizah Y. Chenia; Sabiha Y. Essack (Antibiotics, 2020)
The increased use of antibiotics in food animals has resulted in the selection of drug-resistant bacteria across the farm-to-fork continuum. This study aimed to investigate the molecular epidemiology of antibiotic-resistant Escherichia coli from intensively produced poultry in the uMgungundlovu District, KwaZulu-Natal, South Africa. Samples were collected weekly between August and September 2017 from hatching to final retail products. E. coli was isolated on eosin methylene blue agar, identified biochemically, and confirmed using polymerase chain reaction (PCR). Susceptibility to 19 antibiotics was ascertained by the Kirby–Bauer disc diffusion method. PCR was used to test for resistance genes. The clonal similarity was investigated using enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR). In total, 266 E. coli isolates were obtained from all the samples, with 67.3% being non-susceptible to at least one antibiotic tested and 6.7% multidrug resistant. The highest non-susceptibility was to ampicillin (48.1%) and the lowest non-susceptibility to ceftriaxone and azithromycin (0.8%). Significant non-susceptibility was observed to tetracycline (27.4%), nalidixic acid (20.3%), trimethoprim-sulfamethoxazole (13.9%), and chloramphenicol (11.7%) which have homologues used in the poultry industry. The most frequently observed resistance genes were blaCTX-M (100%), sul1 (80%), tetA (77%), and tetB (71%). ERIC-PCR grouped isolates into 27 clusters suggesting the spread of diverse clones across the farm-to-fork continuum. This reiterates the role of intensive poultry farming as a reservoir and a potential vehicle for the transmission of antibiotic resistance, with potentially severe public health implications, thus, requiring prompt and careful mitigation measures to protect human and environmental health.